(untitled) (GIST – Education and Learning Research Journal, 2021)
This article reports on a mixed-methods research study in five English Language Teaching Master’s programs in Colombia. The purpose was to identify research problems as well as the strategies of intervention that M.A candidates and alumni dealt with in their theses. This study identified prevalent research methods, techniques, and instruments. The data collection methods included documentary analysis, four focus groups with students, four informal talks with the faculty, four interviews with the coordinators of the programs, and surveys with graduate students, professors, thesis advisors and administrators of these programs. Results suggest a preference for action research on issues of language skills, curriculum design, cognitive and affective factors. Pedagogical innovations dealt with ICT, ELT methods, and language learning strategies. Another result indicated that program participants considered the master’s as the most enriching professional development opportunity they have had. This study makes a call to local and national governments to continue funding continued graduate education and to make it a policy independent of partisan agendas.